Route generation for optimization in the Air Transport System : aircraft recovery problem and 4D trajectory planning - Qian, Xiongwen (2018)
The punctuality and efficiency of the Air Transport System (ATS) has a significant impact on the economy. In 2016, the US Passenger Carrier Delay Costs were estimated to be USD 62.55 per minute and the total US flight arrival delays amounted to over 59 million minutes. Furthermore, air traffic volume is growing rapidly. The International Civil Aviation Organization (ICAO) estimates that air traffic in the Asia Pacific region will triple by 2030. With the rapid growth of air traffic, the inefficiency of the ATS has become a salient problem. Flight delays, cancellations, and air traffic congestion cost customers and airlines a considerable amount of money. In this dissertation, we tackle the inefficiency of the ATS from two perspectives: airspace users (airlines) and Air Traffic Management (ATM) service providers (air traffic controllers). Correspondingly, two critical problems are studied on the operational level, the aircraft recovery problem (ARP) and 4D (three dimensions plus time) trajectory planning. Both problems are formulated as special routing problems, and because of the large computational scale of the two problems encountered in real life, they are solved by carefully designed route generation algorithms employing ad hoc decomposition techniques.